2004
DOI: 10.1111/j.0022-2445.2004.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Practices as Moderators of the Relationship Between Peers and Adolescent Marijuana Use

Abstract: We address how childcare subsidies help in the welfare-to-work transition relative to other factors. We examine how the policy operates, whether childcare problems differ by subsidy receipt, and the effect of subsidy on work. Data are from a random sample panel study of welfare recipients after 1996. Findings show that subsidy receipt reduces costs but not parenting stress or problems with care. It predicts earnings and work duration net of other factors. Increased use of subsidies by eligible families and gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 51 publications
4
22
0
Order By: Relevance
“…In general, these studies have found that when parents know who their children are with, where they are, and when they will return (parental monitoring and/or knowledge), children show fewer externalizing behaviors, associate with fewer delinquent peers, and are less likely to initiate use of drugs. This pattern of findings has been shown for initiation of commonly used substances like tobacco, alcohol, and marijuana (Crano, Siegel, Alvaro, Lac, & Hemovich, 2008; Dishion et al, 1995; Dishion & Loeber, 1985; Dorius, Bahr, Hoffmann, & Harmon, 2004; Duncan, Duncan, Biglan, & Ary, 1998; Lac & Crano, 2009; Piko & Kovacs, 2010) as well as for use of other less commonly used drugs, like ecstasy (Martins, Storr, Alexandre, & Chilcoat, 2008; Wu, Liu, & Fan, 2010) and inhalants (Nonnemaker, Crankshaw, Shive, Hussin, & Farrelly, 2011). Although other parenting behaviors (i.e., hostility, warmth, involvement, and coercive discipline) have also been shown to predict adolescent substance use (e.g., Cheng & Lo, 2010; Fletcher, Steinberg, & Williams-Wheeler, 2004; Siebenbruner, Englund, Egeland, & Hudson, 2006), generally parental monitoring and knowledge continues to be a significant predictor above and beyond other parenting behaviors (see Chen, Storr, & Anthony, 2005 for an exception to this).…”
Section: Family Relationships and Drug Initiationmentioning
confidence: 65%
“…In general, these studies have found that when parents know who their children are with, where they are, and when they will return (parental monitoring and/or knowledge), children show fewer externalizing behaviors, associate with fewer delinquent peers, and are less likely to initiate use of drugs. This pattern of findings has been shown for initiation of commonly used substances like tobacco, alcohol, and marijuana (Crano, Siegel, Alvaro, Lac, & Hemovich, 2008; Dishion et al, 1995; Dishion & Loeber, 1985; Dorius, Bahr, Hoffmann, & Harmon, 2004; Duncan, Duncan, Biglan, & Ary, 1998; Lac & Crano, 2009; Piko & Kovacs, 2010) as well as for use of other less commonly used drugs, like ecstasy (Martins, Storr, Alexandre, & Chilcoat, 2008; Wu, Liu, & Fan, 2010) and inhalants (Nonnemaker, Crankshaw, Shive, Hussin, & Farrelly, 2011). Although other parenting behaviors (i.e., hostility, warmth, involvement, and coercive discipline) have also been shown to predict adolescent substance use (e.g., Cheng & Lo, 2010; Fletcher, Steinberg, & Williams-Wheeler, 2004; Siebenbruner, Englund, Egeland, & Hudson, 2006), generally parental monitoring and knowledge continues to be a significant predictor above and beyond other parenting behaviors (see Chen, Storr, & Anthony, 2005 for an exception to this).…”
Section: Family Relationships and Drug Initiationmentioning
confidence: 65%
“…For example, Vitaro, Brendgen, and Tremblay (2000) observed that boys’ attachment to parents moderated the link between best friend’s deviancy and their own later delinquency. Dorius, Bahr, Hoffmann, and Harmon (2004) also reported that closeness to a parent moderated the relationship between peer drug use and adolescent marijuana use.…”
Section: Social Support and The Snares Of Gang Affiliationmentioning
confidence: 96%
“…Dishion (2003) and others (Dorius, Bahr, Hoffman, & Harmon, 2004; Fletcher, Steinberg, & Williams-Wheeler, 2004; Melby, Conger, Conger, & Lorenz, 1993) have linked rewards for prosocial behavior to reduced youth antisocial behavior. A closely related set of parenting behaviors is the ability to do problem solving with their teen without hostility or protracted argument.…”
Section: Observed Parenting Behavior With Teens: Measurement Invarianmentioning
confidence: 99%